FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI PROVINSI NUSA TENGGARA TIMUR MENGGUNAKAN METODE ANALISIS JALUR - Bernadinus Legimin; Astri Atti; Ariyanto Ariyanto (JURNAL DIFERENSIAL, 2023)
An indicator for human quality of life is The Human Development Index (HDI). Factors to be included for measuring HDI are life expectancy, long-term school expectancy, average length of schooling. In this study, path analysis has been applied to determine the magnitude of the influence of these factors on the human development index. Results showed that the structural equation of the formed path diagram is: Y=0,341X1+0,289X2 +0,593X3+0,315. Each addition of life expectancy (X1) by 1 year will increase the human development index (Y) by 34.1% if other variables are constant, every addition of old school expectations (X2) by 1 year will increase the human development index (Y) by 28.9% if other variables are constant, each addition of the average length of schooling (X3) by 1 year will increase the human development index (Y) by 59.3% if other variables are constant. Life Expectancy (X_1), Old School Expectancy (X2) and Average Length of Schooling (X3) affect the Human Development Index (Y).